Republic of Malawi Poverty Assessment - World Bank Group (World Bank, Washington, DC, 2017)
Malawi’s monetary poverty is high and did not lessen in rural areas between 2004 and 2010. The over-representation of poverty in rural settings kept national poverty stagnant. Furthermore, the majority of the rural population, especially the bottom 40%, remained deprived of access to key durable assets and key public services including electricity and running water. In contrast, wealthier households and those located in urban areas tended to enjoy higher access to key assets, services, and opportunities. These gaps associated with socioeconomic status and location can impair a person’s ability to perform well later in life and are likely to perpetuate poverty in rural Malawi. It is imperative that Malawi provide services and opportunities more inclusively.